Perovskite photoelectric conversion device, perovskite solar cell including same, and method of manufacturing same

By introducing an intermediate layer into a perovskite solar cell, the interface characteristics of the perovskite light absorption layer and the electron transport layer are improved by using the thermal evaporation process, the perovskite surface defects and energy mismatch problems are solved, and the photoelectric conversion efficiency and stability are improved.

CN120530735APending Publication Date: 2025-08-22HANWHA SOLUTIONS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480006705.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-04
Filing Date
2024-01-03
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

In existing perovskite solar cells, the perovskite surface defects caused by solution processes and the energy mismatch between perovskite and C60 affect the open circuit voltage, fill factor and stability of the device.

Method used

The intermediate layer is introduced between the perovskite light absorption layer and the electron transport layer through the thermal evaporation process, and materials such as lead sulfate, lead phosphate, lead carbonate, lead chromate or lead oxalate are used to improve the interface characteristics.

Benefits of technology

It improves the photoelectric conversion efficiency and long-term stability, solves the coverage and thickness uniformity problems caused by the solution process, and improves the energy matching between perovskite and the electron transport layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120530735A_ABST
    Figure CN120530735A_ABST
Patent Text Reader

Abstract

The present invention relates to a perovskite photoelectric conversion device, a perovskite solar cell including the same, and a method of manufacturing the same, the perovskite photoelectric conversion device having an intermediate layer introduced on one side of a perovskite light absorbing layer by thermal vapor deposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a perovskite photoelectric conversion device in which an intermediate layer is introduced onto one surface of a perovskite light absorbing layer by a thermal evaporation process, a solar cell including the same, and a method for manufacturing the same. Background Art

[0002] Solar cells convert solar energy into electrical energy and generate electrical energy by utilizing the photovoltaic effect in which electrons and holes are generated by absorbing solar energy.

[0003] Various types of solar cells have been proposed, among which solar cells using a perovskite material, which is a material known to have the same crystal structure as calcium titanium oxide (CaTiO 3 ), as a light absorbing layer have attracted attention.

[0004] Perovskite solar cells are third-generation solar cells that combine thin-film technology and have advantages over other types of solar cells, such as high absorption coefficient, variable band gap, and fast growth rate. Furthermore, perovskite solar cells are superior to silicon solar cells in terms of price, strength, weight, and efficiency.

[0005] Meanwhile, the perovskites used in solar cells typically have a three-dimensional crystal structure, and the perovskites with this crystal structure are used for the light absorbing layer. In addition, solar cells typically have a structure in which an electron transport layer and a hole transport layer are arranged on both sides of the perovskite light absorbing layer with a three-dimensional crystal structure.

[0006] The perovskite light absorbing layer having a three-dimensional crystal structure is usually formed as a thin film by applying a solution process or a deposition process. Pb is generated on the surface and / or top of the perovskite formed as above. + defects, which reduces the open circuit voltage (V oc ). In addition, in a specific device structure (pin structure), there is a C 60 The energy mismatch problem of the materials reduces the fill factor (FF) of the solar cell device. To solve this problem, previous studies have attempted to solve the above problem by coating the perovskite surface with an ammonium-based material (which is an A-site material capable of forming a 2D perovskite) through a solution process to remove defects on its top and / or surface. In the nip-type perovskite solar cell structure, the open circuit voltage (V oc ) and fill factor (FF), but in the pin-type perovskite solar cell structure, due to the formed 2D perovskite material and the subsequent electron transport layer (ETL layer) namely C 60 The energy mismatch between them will cause a short-circuit current density (J SC ) and another problem of fill factor (FF) degradation.

[0007] Therefore, in order to improve the C 60 Due to the energy mismatch of the materials, a LiF layer is applied between the perovskite light absorption layer and the electron transport layer to improve the open circuit voltage (V OC ) and fill factor (FF). However, there is no improvement in defect removal on the perovskite surface, and Li + The separation of ions from the LiF material leads to a decrease in the stability of the solar cell device.

[0008] In order to overcome the above problems, Figure 1 As shown, by using (C8H 17 NH3)2SO4 solvent coats the top surface of the perovskite to form a thin film to solve the problem of Pb + Defects and pin structures in perovskite and C 60 However, there are some problems such as the energy mismatch between + Reaction of SO4 2- Unreacted (C8H 17 NH3) 2+ Problems include surface contamination caused by residues, coverage limitations of solution processes, and thickness uniformity limitations. Summary of the Invention

[0009] Technical issues

[0010] In order to overcome the above problems, the present invention aims to provide a perovskite photoelectric conversion device, a perovskite solar cell including the same, and a method for manufacturing the same. The perovskite photoelectric conversion device introduces a thermal evaporation process to introduce an intermediate layer on top of the perovskite light absorption layer, which can solve the coverage problem caused by the solution process, the limitations caused by thickness adjustment, and the limitations caused by residual unreacted materials.

[0011] Furthermore, the present invention aims to provide a perovskite photoelectric conversion device having excellent photoelectric conversion efficiency and durability, a perovskite solar cell including the same, and a method for manufacturing the same.

[0012] Technical Solution

[0013] In order to achieve the above-mentioned purpose, the method of manufacturing a perovskite photoelectric conversion device of the present invention may include: a first step of forming a hole transport layer on top of a first electrode, a second step of forming a perovskite light absorption layer on top of the hole transport layer, a third step of forming an intermediate layer on top of the perovskite light absorption layer by a thermal evaporation process, a fourth step of forming an electron transport layer on top of the intermediate layer, and a fifth step of forming a second electrode on top of the electron transport layer.

[0014] As an exemplary embodiment of the present invention, the intermediate layer may include one or more selected from lead sulfate (PbSO4), lead phosphate (Pb3(PO4)2), lead carbonate (PbCO3), lead chromate (PbCrO4) and lead oxalate (PbC2O4).

[0015] As an exemplary embodiment of the present invention, the intermediate layer may include lead sulfate (PbSO 4 ).

[0016] As an exemplary embodiment of the present invention, lead sulfate may be prepared by reacting lead nitrate (Pb(NO 3 ) 2 ) with sodium sulfate (Na 2 SO 4 ).

[0017] As an exemplary embodiment of the present invention, lead sulfate may be prepared by reacting lead nitrate (Pb(NO 3 ) 2 ) with sodium sulfate (Na 2 SO 4 ) at a molar ratio of 1:0.8 to 1.2.

[0018] As an exemplary embodiment of the present invention, a thickness ratio of the perovskite light absorbing layer and the intermediate layer may be 1:0.0005 to 0.005.

[0019] As an exemplary embodiment of the present invention, the perovskite light absorbing layer may include a compound represented by Chemical Formula 1:

[0020] [Chemical Formula 1]

[0021] [A][B][X]3

[0022] In Chemical Formula 1, A is a monovalent organic cation, a monovalent metal cation, or a mixed monovalent cation thereof, B is a divalent metal cation, and X is at least one anion.

[0023] The electron transport layer may include a fullerene-based organic material.

[0024] As an exemplary embodiment of the present invention, the fullerene-based organic material may include a member selected from C 60 、C 70 , one or more of PC60BM and PC70BM.

[0025] At the same time, the method for manufacturing a perovskite photoelectric conversion device according to the present invention may include a first step of forming a hole transport layer on top of a first electrode, a second step of forming an organic interface layer on top of the hole transport layer, a third step of forming a perovskite light absorption layer on top of the organic interface layer, a fourth step of forming an intermediate layer on top of the perovskite light absorption layer by a thermal evaporation process, a fifth step of forming an electron transport layer on top of the intermediate layer, and a sixth step of forming a second electrode on top of the electron transport layer.

[0026] In addition, the perovskite photoelectric conversion device of the present invention may include a laminate in which a first electrode, a hole transport layer, a perovskite light absorption layer, an intermediate layer, an electron transport layer and a second electrode are stacked in sequence, and the intermediate layer may contain one or more selected from lead sulfate (PbSO4), lead phosphate (Pb3(PO4)2), lead carbonate (PbCO3), lead chromate (PbCrO4) and lead oxalate (PbC2O4).

[0027] As an exemplary embodiment of the present invention, the intermediate layer may include lead sulfate (PbSO 4 ).

[0028] As an exemplary embodiment of the present invention, a thickness ratio of the perovskite light absorbing layer and the intermediate layer may be 1:0.0005 to 0.005.

[0029] As an exemplary embodiment of the present invention, the electron transport layer may include a fullerene-based organic material.

[0030] As an exemplary embodiment of the present invention, the fullerene-based organic material may include a member selected from C 60 、C 70 , one or more of PC60BM and PC70BM.

[0031] As an exemplary embodiment of the present invention, the laminate may further include an organic interface layer between the hole transport layer and the perovskite light absorbing layer.

[0032] Meanwhile, the perovskite solar cell of the present invention includes the perovskite photoelectric conversion device of the present invention.

[0033] Furthermore, the silicon / perovskite heterojunction tandem solar cell of the present invention may include the perovskite photoelectric conversion device of the present invention.

[0034] Beneficial effects

[0035] According to the perovskite photoelectric conversion device, the perovskite solar cell including the same and the manufacturing method thereof of the present invention, an intermediate layer is introduced between the perovskite light absorption layer and the electron transport layer through a thermal evaporation process, thereby improving the interface characteristics between the perovskite light absorption layer and the electron transport layer, thereby achieving excellent photoelectric conversion efficiency and long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a lead oxyacid salt (C8H 17 Schematic diagram of the solution process for coating the perovskite surface with NH3)2SO4 solvent.

[0037] Figure 2 Schematic diagram showing the formation of an intermediate layer on top of a perovskite photoactive layer by thermal evaporation in the method for manufacturing a perovskite photoelectric conversion device of the present invention.

[0038] Figure 3 : is a figure showing the XRD pattern of the reactant prepared in Preparation Example 1 of the present invention (upper figure) (lower figure is theoretical data). DETAILED DESCRIPTION

[0039] Hereinafter, the present invention will be described in detail.

[0040] In order to improve the C 60 Due to the energy mismatch of the materials, a LiF layer is applied between the perovskite light absorption layer and the electron transport layer to improve the open circuit voltage (V OC ) and fill factor (FF). However, there is no improvement in defect removal on the perovskite surface, and Li + The separation of ions from the LiF material leads to a decrease in the stability of the solar cell device.

[0041] To overcome these problems, the lead oxoacid salt (C8H 17 NH3)2SO4 solvent coats the top surface of the perovskite to form a thin film, solving the problem of Pb + Defects and pin structures in perovskite and C 60 However, there are some problems such as the energy mismatch between + Reaction of SO4 2- Unreacted (C8H 17 NH3) 2+ Problems include surface contamination caused by residues, coverage limitations of solution processes, and thickness uniformity limitations.

[0042] Therefore, in the present invention, since an intermediate layer is introduced between the perovskite light absorbing layer and the electron transport layer by a thermal evaporation process, the interface characteristics between the perovskite light absorbing layer and the electron transport layer are improved, thereby achieving excellent photoelectric conversion efficiency and long-term stability.

[0043] The method for manufacturing a perovskite photoelectric conversion device of the present invention includes first to fifth steps.

[0044] First, in the first step of the method for manufacturing a perovskite photoelectric conversion device of the present invention, a hole transport layer may be formed on top of the first electrode.

[0045] The first electrode may include a conductive transparent substrate and a transparent thin film of ITO (indium tin oxide), FTO (fluorine-doped tin oxide), ATO (Sb2O3-doped tin oxide), GTO (gallium-doped tin oxide), ZTO (tin-doped zinc oxide), ZTO:Ga (gallium-doped ZTO), IGZO (indium gallium zinc oxide), IZO (indium-doped zinc oxide) or AZO (aluminum-doped zinc oxide) may be deposited thereon.

[0046] In addition, the thickness of the first electrode is, but not limited to, preferably 50 nm to 200 nm, and more preferably 100 nm to 170 nm.

[0047] The hole transport layer (HTL) is a layer that transports holes formed in the below-described perovskite light absorbing layer and blocks the movement of electrons, and may include an inorganic and / or organic hole transport material.

[0048] Here, the inorganic hole transport material may include nickel oxide (NiO x ), one or more of CuSCN, CuCrO2, CuI, MoO and V2O5.

[0049] In addition, the organic hole transport material may include one or more selected from the group consisting of carbazole derivatives, polyarylalkane derivatives, phenylenediamine derivatives, arylamine derivatives, amino-substituted chalcone derivatives, styrylanthracene derivatives, fluorene derivatives, hydrazone derivatives, stilbene derivatives, silazane derivatives, aromatic tertiary amine compounds, styrylamine compounds, aromatic dimethylidine-based compounds, porphyrin-based compounds, phthalocyanine-based compounds, polythiophene derivatives, polypyrrole derivatives, polyparaphenylenevinylene derivatives, pentacene, coumarin 6 (3-(2-benzothiazolyl)-7-(diethylamino)coumarin), ZnPC (zinc phthalocyanine), CuPC (copper phthalocyanine), TiOPC (titanium phthalocyanine oxide), spiro-MeOTAD (2,2',7,7'-tetrakis(N,N-dimethoxyphenylamino)-9,9'-spirobifluorene), F16CuPC (1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexafluoro-29H,31H-phthalocyanine copper(II)), SubPc (boron subphthalocyanine chloride), cis-bis(thiocyanato)-bis(2,2'-bipyridine-4,4'-dicarboxylate)-ruthenium(II) (N3), P3HT (poly[3-hexylthiophene]), MDMO-PPV (poly[2-methoxy-5-(3',7'-dimethylthiophene)] [1,4-dioctyl fluorene]]-1,4-phenylene vinylene), MEH-PPV (poly[2-methoxy-5-(2″-ethylhexyloxy)-p-phenylene vinylene]), P3OT (poly(3-octylthiophene)), POT (poly(octylthiophene)), P3DT (poly(3-decylthiophene)), P3DDT (poly(3-dodecylthiophene)), PPV (poly(p-phenylene vinylene)), TFB (poly(9,9′-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine)), polyaniline, spiro-MeOTAD ([2,22′,7,77′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9,9′-spirobifluorene]), PCPDTBT (poly[2,1,3-benzothiadiazole- 4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]]), Si-PCPDTBT(poly[(4,4'-bis(2-ethylhexyl)dithieno[3,2-b:2',3'-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl]), PBDTTPD(poly[(4,8-diethylhexyloxy)), PFDTBT(poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4',7-di-2-thienyl-2',1',3'-benzothiadiazole)]), PFO-DBT(poly[2,7-.9,9-(dioctyl-fluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)]), PSiFDTBT (poly[(2,7-dioctylsilylfluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5'-diyl]), PCDTBT (poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thienyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thienyl]), PFB( Poly(9,9′-dioctylfluorene-co-bis(N,N′-(4-butylphenyl))bis(N,N′-phenyl-1,4-phenylene)diamine), F8BT (poly(9,9′-dioctylfluorene-co-benzothiadiazole)), PEDOT (poly(3,4-ethylenedioxythiophene)), PEDOT:PSS (poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate)), PTAA (poly(triarylamine)), 2-PACz, MeO-2PACz, Br-2PACz, Me-4PACz, MeO-4PACz, and 6-PACz.

[0050] In addition, as a method for forming the hole transport layer, a coating method and a vacuum deposition method may be used, and the coating method may include gravure coating, bar coating, printing, spray coating, spin coating, dipping, and die coating.

[0051] In addition, the thickness of the hole transport layer is, but not limited to, preferably 5 nm to 50 nm, and more preferably 10 nm to 40 nm.

[0052] Next, the second step of the method for manufacturing a perovskite photoelectric conversion device of the present invention may be to form a perovskite light absorbing layer on top of the hole transport layer.

[0053] The perovskite light absorbing layer may include a general perovskite material applied to a light absorbing layer of a solar cell, and the perovskite having a 3D crystal structure may include a perovskite material that absorbs light with a wavelength of 300 nm to 800 nm. As an exemplary embodiment, the compound represented by the following Chemical Formula 1 may be included.

[0054] [Chemical Formula 1]

[0055] [A][B][X]3

[0056] In Chemical Formula 1, A is a monovalent organic cation, a monovalent metal cation, or a mixed monovalent cation thereof, B is a divalent metal cation, and X is at least one anion.

[0057] Specifically, A may include amines, ammonium, Group 1 metals, Group 2 metals and / or other cations or quasi-cationic compounds, and preferably formamidine (FA), methylammonium (MA), FAMA, CsFAMA, CsFA or N(R)4 + (Here, R may be the same or different groups, and R is a C1 to C5 linear alkyl group, a C3 to C5 branched alkyl group, a phenyl group, an alkylphenyl group, an alkoxyphenyl group, or an alkyl halide).

[0058] In addition, B may include one or two selected from Fe, Co, Ni, Cu, Sn, Pb, Bi, Ge, Ti, Eu, and Zr.

[0059] In addition, X may include one or more halogen elements and / or Group 16 anions selected from F, Cl, Br, and I, and preferably, X may be I x Br 3-x (0≤x≤3).

[0060] At the same time, the perovskite light absorption layer may be a single layer composed of the same perovskite material, or may be a multilayer structure formed by stacking multiple layers composed of different perovskite materials, and the light absorption layer composed of one type of perovskite material may include one type of perovskite material and a perovskite material of a different type from the one type of perovskite material, which has a columnar (e.g., cylindrical), plate-like, needle-like, linear or rod-like shape.

[0061] In addition, to form the perovskite light absorbing layer, a coating method and a vacuum deposition method may be used, and the coating method may include gravure coating, bar coating, printing, spray coating, spin coating, dipping, inkjet coating, and die coating.

[0062] Next, if Figure 2 As shown, the third step of the method for manufacturing a perovskite photoelectric conversion device of the present invention can be to form an intermediate layer 20 on top of the perovskite light absorbing layer 10 by a thermal evaporation process. The present invention not only removes defects on the surface of the perovskite light absorbing layer, but also introduces the intermediate layer by the thermal evaporation process to guide the energy matching with the electron transport layer described later in the appropriate direction.

[0063] Specifically, the intermediate layer may include one or more selected from lead sulfate (PbSO4), lead phosphate (Pb3(PO4)2), lead carbonate (PbCO3), lead chromate (PbCrO4) and lead oxalate (PbC2O4), and preferably lead sulfate (PbSO4).

[0064] Here, lead sulfate can be prepared by reacting lead nitrate (Pb(NO3)2) with sodium sulfate (Na2SO4), preferably by reacting lead nitrate (Pb(NO3)2) with sodium sulfate (Na2SO4) at a molar ratio of 1:0.9 to 1.1, and more preferably at a molar ratio of 1:0.95 to 1.05. When the molar ratio is less than 1:0.9, the problem of reduced yield may occur, and when the molar ratio is greater than 1:1.1, the problem of extracting a high-purity final reaction product may occur.

[0065] At the same time, the thickness ratio of the perovskite light absorption layer 10 and the intermediate layer 20 of the present invention can be 1:0.0005 to 0.005, and preferably 1:0.001 to 0.003; when the thickness ratio is less than 0.0005, there may be problems with energy matching and coverage with the electron transport layer described later, and when the thickness ratio exceeds 0.005, the current of the solar cell may decrease due to increased insulation properties.

[0066] Next, the fourth step of the method for manufacturing a perovskite photoelectric conversion device of the present invention may be to form an electron transport layer on top of the intermediate layer.

[0067] The electron transport layer (ETL) is a layer that transports electrons formed in the perovskite light absorbing layer and blocks the movement of holes, and may include a fullerene-based organic material. Here, the fullerene-based organic material may include a C 60 、C 70 , PC60BM and PC70BM, and preferably C 60 .

[0068] In addition, in order to form the electron transport layer, a coating method and a vacuum deposition method may be used, and the coating method may include gravure coating, bar coating, printing, spray coating, spin coating, dipping, and die coating.

[0069] In addition, the thickness of the electron transport layer is, but not limited to, preferably 5 nm to 30 nm, and more preferably 10 nm to 15 nm.

[0070] Finally, the fifth step of the method for manufacturing a perovskite photoelectric conversion device of the present invention may be to form a second electrode on top of the electron transport layer.

[0071] The second electrode can be formed by depositing a metal material through a deposition process, preferably a thermal evaporation process.

[0072] Here, the metal material may include one or more selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, Os, C, and a conductive polymer.

[0073] In addition, the thickness of the second electrode is, but not limited to, preferably 50 nm to 2.5 μm, and more preferably 80 nm to 150 nm.

[0074] Meanwhile, another method for manufacturing a perovskite photoelectric conversion device of the present invention may include a first step of forming a hole transport layer on top of a first electrode, a second step of forming an organic interface layer on top of the hole transport layer, a third step of forming a perovskite light absorption layer on top of the organic interface layer, a fourth step of forming an intermediate layer on top of the perovskite light absorption layer by a thermal evaporation process, a fifth step of forming an electron transport layer on top of the intermediate layer, and a sixth step of forming a second electrode on top of the electron transport layer.

[0075] Specifically, unlike the above-mentioned method of manufacturing a perovskite photoelectric conversion device of the present invention, an organic interface layer can be formed between the hole transport layer and the perovskite light absorption layer, and the organic interface layer can be used to improve hole transport capability and prevent recombination.

[0076] The organic interface layer may include an aromatic compound having a double bond, and preferably may include one or more selected from pyridine, aniline, carbazole, phenazine, phenoxazine, and phenothiazine. In addition, pyridine, aniline, carbazole, phenazine, phenoxazine, or phenothiazine may have another alkyl group attached at a carbon, oxygen, or nitrogen site, and the terminal of the alkyl group may include a carboxylic acid, phosphorous acid, R4N + A halide anion group (here, R may be H or C), or a group such as a sulfonate.

[0077] In addition, in order to form the organic interface layer, a coating method and a vacuum deposition method may be used, and the coating method may include gravure coating, bar coating, printing, spray coating, spin coating, dipping, and die coating.

[0078] In addition, the thickness of the organic interface layer is, but not limited to, preferably 1 nm to 10 nm, and more preferably 1 nm to 3 nm.

[0079] In addition, the perovskite photoelectric conversion device of the present invention may include a laminate in which a first electrode, a hole transport layer, a perovskite light absorbing layer, an intermediate layer, an electron transport layer, and a second electrode are stacked in this order. Here, the first electrode, the hole transport layer, the perovskite light absorbing layer, the intermediate layer, the electron transport layer, and the second electrode are as described above.

[0080] In addition, the intermediate layer may include one or more selected from lead sulfate (PbSO4), lead phosphate (Pb3(PO4)2), lead carbonate (PbCO3), lead chromate (PbCrO4) and lead oxalate (PbC2O4), and preferably lead sulfate (PbSO4).

[0081] In addition, the thickness ratio of the perovskite light absorbing layer and the intermediate layer of the present invention may be 1:0.0005 to 0.005, and preferably 1:0.001 to 0.003.

[0082] Furthermore, the electron transport layer may comprise a fullerene-based organic material, and is preferably selected from C 60 、C 70 , one or more of PC60BM and PC70BM.

[0083] In addition, the laminate may further include an organic interface layer between the hole transport layer and the perovskite light absorbing layer, and the organic interface layer is as described above.

[0084] Meanwhile, the perovskite solar cell of the present invention may include the perovskite photoelectric conversion device of the present invention.

[0085] Furthermore, the silicon / perovskite heterojunction tandem solar cell of the present invention may include the perovskite photoelectric conversion device of the present invention.

[0086] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the following Examples are not intended to limit the scope of the present invention, but should only be interpreted as illustrations to help understand the present invention.

[0087] Preparation Example 1: Preparation of composition for intermediate layer

[0088] A reactant was prepared by placing 25 g (75.48 mmol) of lead nitrate (Pb(NO3)2), 10.72 g (75.48 mmol) of sodium sulfate (Na2SO4) and 50 mL of distilled water in a 250 mL flask and stirring the mixture for 1 hour. The reactant was filtered using a pressure filter apparatus, washed three times with 100 mL of distilled water, and subjected to XRD analysis. As a result, Figure 3 As shown, it was confirmed that lead sulfate (PbSO4) was prepared as a reactant, and the yield thereof was 96%.

[0089] Example 1: Fabrication of a Perovskite Photoelectric Conversion Device

[0090] (1) Prepare an ITO conductive transparent substrate with a size of 2.5 cm (W) × 2.5 cm (L) × 100 nm (T) as the first electrode. Immerse the prepared ITO conductive transparent substrate in a sodium hydroxide cleaning solution and subject it to ultrasonic cleaning for 1 hour. Then, wash the resulting substrate again with distilled water and ethanol and dry it with nitrogen. The cleaned and dried ITO conductive transparent substrate is partially etched with an IR laser, and then a hole transport layer (NiO) with a thickness of 30 nm is formed on the top of the ITO conductive transparent substrate by vacuum sputtering deposition. x ).

[0091] (2) Next, 200 μL of a solution for forming an organic interface layer was added dropwise onto the hole transport layer, followed by spin coating at 3000 rpm for 30 seconds and heat treatment at 100°C for 20 minutes to form an organic interface layer having a thickness of 2 nm. Here, ethanol containing 1 mM 4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) was used as the solution for forming the organic interface layer.

[0092] (3) Next, 100 μL of a perovskite crystal structure (Cs 0.2 FA 0.8 Pb(I 0.8 Br 0.2 )3) was prepared by spin coating the 1.3 M perovskite precursor solution at 5000 rpm for 30 seconds in a 99% pure nitrogen atmosphere, and heat-treated at 100° C. for 20 minutes to form a perovskite light absorption layer with a thickness of 500 nm.

[0093] (4) Next, a 1 nm thick intermediate layer was formed on top of the perovskite light absorbing layer by a thermal evaporation process using a thermal evaporation apparatus. Here, lead sulfate (PbSO4) prepared in Preparation Example 1 was used as the intermediate layer forming material.

[0094] (5) Next, C is deposited on top of the intermediate layer by vacuum deposition. 60 Fullerene forms an electron transport layer with an average thickness of 13 nm.

[0095] (6) Next, an exciton blocking layer was formed by dropping 200 μL of a solution in which 1 mg of bathocuproine was dissolved in 1 mL of isopropyl alcohol onto the electron transport layer, spin coating at 4000 rpm for 30 seconds, and heat treating at 100° C. for 20 minutes.

[0096] (7) Finally, a second electrode (Ag) with a thickness of 100 nm was formed on top of the exciton blocking layer by a thermal evaporation process using a thermal evaporation apparatus, thereby completing the fabrication of the perovskite photoelectric conversion device.

[0097] Comparative Example 1: Fabrication of a Perovskite Photoelectric Conversion Device

[0098] (1) Prepare an ITO conductive transparent substrate with a size of 2.5 cm (W) × 2.5 cm (L) × 100 nm (T) as the first electrode. Immerse the prepared ITO conductive transparent substrate in a sodium hydroxide cleaning solution and subject it to ultrasonic cleaning for 1 hour. Then, wash the resulting substrate again with distilled water and ethanol and dry it with nitrogen. The cleaned and dried ITO conductive transparent substrate is partially etched with an IR laser, and then a hole transport layer (NiO) with a thickness of 30 nm is formed on the top of the ITO conductive transparent substrate by vacuum sputtering deposition. x ).

[0099] (2) Next, 200 μL of a solution for forming an organic interface layer was added dropwise onto the hole transport layer, followed by spin coating at 3000 rpm for 30 seconds and heat treatment at 100°C for 20 minutes to form an organic interface layer having a thickness of 2 nm. Here, ethanol containing 1 mM 4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) was used as the solution for forming the organic interface layer.

[0100] (3) Next, 100 μL of a perovskite crystal structure (Cs 0.2 FA 0.8 Pb(I 0.8 Br 0.2 )3) was prepared by spin coating at 5000 rpm for 30 seconds in a 99% pure nitrogen atmosphere, and heat-treated at 100° C. for 20 minutes to form a perovskite light absorbing layer with a thickness of 500 nm.

[0101] (4) Next, a 1 nm thick intermediate layer was formed on top of the perovskite light absorbing layer by a thermal evaporation process using a thermal evaporation apparatus. Here, lithium fluoride (LiF) was used as the intermediate layer forming material.

[0102] (5) Next, C is deposited on top of the intermediate layer by vacuum deposition. 60 Fullerene forms an electron transport layer with an average thickness of 13 nm.

[0103] (6) Next, an exciton blocking layer was formed by dropping 200 μL of a solution in which 1 mg of bathocuproin was dissolved in 1 mL of isopropyl alcohol on the electron transport layer, spin coating at 4000 rpm for 30 seconds, and heat treating at 100° C. for 20 minutes.

[0104] (7) Finally, a second electrode (Ag) with a thickness of 100 nm was formed on top of the exciton blocking layer by a thermal evaporation process using a thermal evaporation apparatus, thereby completing the fabrication of the perovskite photoelectric conversion device.

[0105] Comparative Example 2: Fabrication of a Perovskite Photoelectric Conversion Device

[0106] (1) Prepare an ITO conductive transparent substrate with a size of 2.5 cm (W) × 2.5 cm (L) × 100 nm (T) as the first electrode. Immerse the prepared ITO conductive transparent substrate in a sodium hydroxide cleaning solution and subject it to ultrasonic cleaning for 1 hour. Then, wash the resulting substrate again with distilled water and ethanol and dry it with nitrogen. The cleaned and dried ITO conductive transparent substrate is partially etched with an IR laser, and then a hole transport layer (NiO) with a thickness of 30 nm is formed on the top of the ITO conductive transparent substrate by vacuum sputtering deposition. x ).

[0107] (2) Next, 200 μL of a solution for forming an organic interface layer was added dropwise onto the hole transport layer, followed by spin coating at 3000 rpm for 30 seconds and heat treatment at 100°C for 20 minutes to form an organic interface layer having a thickness of 2 nm. Here, ethanol containing 1 mM 4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) was used as the solution for forming the organic interface layer.

[0108] (3) Next, 100 μL of a perovskite crystal structure (Cs 0.2 FA 0.8 Pb(I 0.8 Br 0.2 )3) was prepared by spin coating at 5000 rpm for 30 seconds in a 99% pure nitrogen atmosphere, and heat-treated at 100° C. for 20 minutes to form a perovskite light absorbing layer with a thickness of 500 nm.

[0109] (4) Next, a 2 mM solution of octylamine and hydroperoxide (H2O4) was prepared by diluting them in chloroform. 200 μL of the prepared 2 mM solution was dropped onto the organic interface layer and spin-coated at 3000 rpm for 30 seconds. The layer was then heat-treated at 100°C for 20 minutes to form a 1 nm thick lead oxoate intermediate layer.

[0110] (5) Next, C is deposited on top of the intermediate layer by vacuum deposition. 60 Fullerene forms an electron transport layer with an average thickness of 13 nm.

[0111] (6) Next, an exciton blocking layer was formed by dropping 200 μL of a solution in which 1 mg of bathocuproin was dissolved in 1 mL of isopropyl alcohol on the electron transport layer, spin coating at 4000 rpm for 30 seconds, and heat treating at 100° C. for 20 minutes.

[0112] (7) Finally, a second electrode (Ag) with a thickness of 100 nm was formed on top of the exciton blocking layer by a thermal evaporation process using a thermal evaporation apparatus, thereby completing the fabrication of the perovskite photoelectric conversion device.

[0113] Comparative Example 3: Fabrication of a Perovskite Photoelectric Conversion Device

[0114] (1) Prepare an ITO conductive transparent substrate with a size of 2.5 cm (W) × 2.5 cm (L) × 100 nm (T) as the first electrode. Immerse the prepared ITO conductive transparent substrate in a sodium hydroxide cleaning solution and subject it to ultrasonic cleaning for 1 hour. Then, the resulting substrate is cleaned again with distilled water and ethanol and dried using nitrogen. The cleaned and dried ITO conductive transparent substrate is partially etched with an IR laser, and then a hole transport layer (NiO) with a thickness of 30 nm is formed on the top of the ITO conductive transparent substrate by vacuum sputtering deposition. x ).

[0115] (2) Next, 200 μL of a solution for forming an organic interface layer was added dropwise onto the hole transport layer, followed by spin coating at 3000 rpm for 30 seconds and heat treatment at 100°C for 20 minutes to form an organic interface layer having a thickness of 2 nm. Here, ethanol containing 1 mM 4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) was used as the solution for forming the organic interface layer.

[0116] (3) Next, 100 μL of a perovskite crystal structure (Cs 0.2 FA 0.8 Pb(I 0.8 Br 0.2 )3) was prepared by spin coating at 5000 rpm for 30 seconds in a 99% pure nitrogen atmosphere, and heat-treated at 100° C. for 20 minutes to form a perovskite light absorbing layer with a thickness of 500 nm.

[0117] (4) Next, a 4 mM solution of octylamine and hydroperoxide (H2O4) was prepared by diluting them in chloroform. 200 μL of the prepared 4 mM solution was dropped onto the organic interface layer and spin-coated at 3000 rpm for 30 seconds. The layer was then heat-treated at 100°C for 20 minutes to form a 1 nm thick lead oxoate intermediate layer.

[0118] (5) Next, C is deposited on top of the intermediate layer by a vacuum deposition process. 60 Fullerene forms an electron transport layer with an average thickness of 13 nm.

[0119] (6) Next, an exciton blocking layer was formed by dropping 200 μL of a solution in which 1 mg of bathocuproin was dissolved in 1 mL of isopropyl alcohol on the electron transport layer, spin coating at 4000 rpm for 30 seconds, and heat treating at 100° C. for 20 minutes.

[0120] (7) Finally, a second electrode (Ag) with a thickness of 100 nm was formed on top of the exciton blocking layer by a thermal evaporation process using a thermal evaporation apparatus, thereby completing the fabrication of the perovskite photoelectric conversion device.

[0121] Experimental Example 1: Measurement of Perovskite Photoelectric Conversion Device Performance

[0122] For each of the perovskite photoelectric conversion devices manufactured in Example 1 and Comparative Examples 1 to 3, the efficiency was measured based on an initial JV curve obtained using a solar simulator and a JV Keithley instrument, and the measurement results are shown in Table 1 below.

[0123] [Table 1]

[0124]

[0125] As can be seen from Table 1, it can be confirmed that all efficiency parameters of the photoelectric conversion device manufactured in Example 1, in which a uniform thin film of a PbSO4 intermediate layer is formed on the perovskite surface by a thermal evaporation process, are improved compared with the photoelectric conversion devices manufactured in Comparative Examples 1 to 3.

[0126] Comparative Example 4: Fabrication of a Perovskite Photoelectric Conversion Device

[0127] (1) Prepare an ITO conductive transparent substrate with a size of 2.5 cm (W) × 2.5 cm (L) × 100 nm (T) as the first electrode. Immerse the prepared ITO conductive transparent substrate in a sodium hydroxide cleaning solution and subject it to ultrasonic cleaning for 1 hour. Then, wash the resulting substrate again with distilled water and ethanol and dry it with nitrogen. The cleaned and dried ITO conductive transparent substrate is partially etched with an IR laser, and then a hole transport layer (NiO) with a thickness of 30 nm is formed on the top of the ITO conductive transparent substrate by vacuum sputtering deposition. x ).

[0128] (2) Next, 200 μL of a solution for forming an organic interface layer was added dropwise onto the hole transport layer, followed by spin coating at 3000 rpm for 30 seconds and heat treatment at 100°C for 20 minutes to form an organic interface layer having a thickness of 2 nm. Here, ethanol containing 1 mM 4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) was used as the solution for forming the organic interface layer.

[0129] (3) Next, 100 μL of a perovskite crystal structure (Cs 0.2 FA 0.8 Pb(I 0.8 Br 0.2 )3) was prepared by spin coating the 1.3 M perovskite precursor solution at 5000 rpm for 30 seconds in a 99% pure nitrogen atmosphere, and heat-treated at 100° C. for 20 minutes to form a perovskite light absorption layer with a thickness of 500 nm.

[0130] (4) Next, C is deposited on top of the perovskite light absorbing layer by vacuum deposition process. 60 Fullerene forms an electron transport layer with an average thickness of 13 nm.

[0131] (5) Next, an exciton blocking layer was formed by dropping 200 μL of a solution in which 1 mg of bathocuproin was dissolved in 1 mL of isopropyl alcohol on the electron transport layer, spin coating at 4000 rpm for 30 seconds, and heat treating at 100° C. for 20 minutes.

[0132] (6) Finally, a second electrode (Ag) with a thickness of 100 nm was formed on top of the exciton blocking layer by a thermal evaporation process using a thermal evaporation apparatus, thereby completing the fabrication of the perovskite photoelectric conversion device.

[0133] Experimental Example 2: Measurement of the Work Function of Perovskite Photoelectric Conversion Devices

[0134] The work functions of the surfaces of the perovskite light absorbing layer of the perovskite photoelectric conversion device manufactured in Comparative Example 4 and the intermediate layer of the perovskite photoelectric conversion device manufactured in Example 1 were obtained by XPS analysis and are shown in Table 2 below.

[0135] [Table 2]

[0136]

[0137] From Table 2, it can be confirmed that the introduction of the intermediate layer reduces the work function (WF) of the perovskite by about 0.5 eV, and this WF reduction effect will be consistent with the effect of the C 60 The energy matching of the electron transport layer composed of fullerene guides it in the appropriate direction.

[0138] Although the embodiments of the present invention are described above, the spirit of the present invention is not limited thereto, and those skilled in the art will understand that various modifications and changes may be made to the present invention by adding, changing or deleting constituent elements without departing from the spirit of the present invention as defined in the appended claims, and such modifications and changes will also be included within the scope of the present invention.

Claims

1. A method for manufacturing a perovskite photoelectric conversion device, comprising: a first step of forming a hole transport layer on top of the first electrode; a second step of forming a perovskite light absorbing layer on top of the hole transport layer; a third step of forming an intermediate layer on top of the perovskite light absorbing layer by a thermal evaporation process; a fourth step of forming an electron transport layer on top of the intermediate layer; and A fifth step is to form a second electrode on top of the electron transport layer.

2. The method according to claim 1, wherein the intermediate layer comprises one or more selected from the group consisting of lead sulfate (PbSO4), lead phosphate (Pb3(PO4)2), lead carbonate (PbCO3), lead chromate (PbCrO4) and lead oxalate (PbC2O4).

3. The method of claim 2, wherein the intermediate layer comprises lead sulfate (PbSO4).

4. The method according to claim 3, wherein the lead sulfate is prepared by reacting lead nitrate (Pb(NO3)2) with sodium sulfate (Na2SO4).

5. The method according to claim 4, wherein the lead sulfate is prepared by reacting lead nitrate (Pb(NO3)2) with sodium sulfate (Na2SO4) in a molar ratio of 1:0.8 to 1.

2. The method according to claim 1 , wherein a thickness ratio of the perovskite light absorbing layer to the intermediate layer is 1:0.0005 to 0.

005.

7. The method according to claim 1, wherein the perovskite light absorbing layer comprises a compound represented by Chemical Formula 1: [Chemical Formula 1] [A][B][X]3 In Chemical Formula 1, A is a monovalent organic cation, a monovalent metal cation, or a mixed monovalent cation thereof, B is a divalent metal cation, and X is at least one anion. The method according to claim 1 , wherein the electron transport layer comprises a fullerene-based organic material.

9. The method according to claim 8, wherein the fullerene-based organic material comprises a member selected from the group consisting of C 60 、C 70 , one or more of PC60BM and PC70BM.

10. A method for manufacturing a perovskite photoelectric conversion device, comprising: a first step of forming a hole transport layer on top of the first electrode; a second step of forming an organic interface layer on top of the hole transport layer; a third step of forming a perovskite light absorbing layer on top of the organic interface layer; a fourth step of forming an intermediate layer on top of the perovskite light absorbing layer by a thermal evaporation process; a fifth step of forming an electron transport layer on top of the intermediate layer; and The sixth step is to form a second electrode on top of the electron transport layer.

11. A perovskite photoelectric conversion device, comprising: A laminate, in which a first electrode, a hole transport layer, a perovskite light absorbing layer, an intermediate layer, an electron transport layer, and a second electrode are sequentially stacked, The intermediate layer comprises one or more selected from lead sulfate (PbSO4), lead phosphate (Pb3(PO4)2), lead carbonate (PbCO3), lead chromate (PbCrO4) and lead oxalate (PbC2O4).

12. The device of claim 11, wherein the intermediate layer comprises lead sulfate (PbSO4). 13 . The device according to claim 11 , wherein a thickness ratio of the perovskite light absorbing layer to the intermediate layer is 1:0.0005 to 0.

005. The device according to claim 11 , wherein the electron transport layer comprises a fullerene-based organic material.

15. The device according to claim 14, wherein the fullerene-based organic material comprises a member selected from the group consisting of C 60 、C 70 , one or more of PC60BM and PC70BM.

16. The device of claim 15, wherein the laminate further comprises an organic interface layer between the hole transport layer and the perovskite light absorbing layer.

17. A perovskite solar cell comprising the perovskite photoelectric conversion device according to claim 11.

18. A silicon / perovskite heterojunction tandem solar cell comprising the perovskite photoelectric conversion device according to claim 11.